Silent angels, the genetic and clinical aspects of Rett syndrome - Dziwota, Ewelina; Fałkowska, Urszula; Adamczyk, Katarzyna; Adamczyk, Dorota; Stefańska, Alena; Pawęzka, Justyna; Olajossy, Marcin (Current Problems of Psychiatry, 2017)
Rett syndrome is a neurodevelopmental genetic disorder and, because of some behavioral characteristics, individuals affected by the disease are known as silent angels. Girls with Rett syndrome perform stereotyped movements, they have learning difficulties, their reaction time is prolonged, and they seem alienated in the environment. These children require constant pediatric, neurological and orthopedic care. In the treatment of Rett syndrome physical therapy, music therapy, hydrotherapy, hippotherapy, behavioral methods, speech therapy and diet, are also used. In turn, psychological therapy of the syndrome is based on the sensory integration method, using two or more senses simultaneously. In 80% of cases, the syndrome is related to mutations of the MECP2 gene, located on chromosome X. The pathogenesis of Rett syndrome is caused by the occurrence of a non-functional MeCP2 protein, which is a transcription factor of many genes, i.e. Bdnf, mef2c, Sgk1, Uqcrc1. Abnormal expression of these genes reveals a characteristic disease phenotype. Clinical symptoms relate mainly to the nervous, respiratory, skeletal and gastrointestinal systems. Currently causal treatment is not possible. However, researchers are developing methods by which, perhaps in the near future, it will be possible to eliminate the mutations in the MECP2 gene, and this will give a chance to the patient for normal functioning. The paper presents the etiology and pathogenesis of the disease, genetic, clinical, pharmacological aspects and other forms of Rett syndrome treatment.